PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VII SMPs ISLAM SAFARI AL-ASMA BAGANSIAPIAPI TAHUN AJARAN2015/2016 - Dede Gusdiana; Irda Sayuti; Wan Syafi’i (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrak: One of the learning that can improve student learning outcomes in learning biology is through cooperative learning of Jigsaw. The purpose of this research to improve learning outcomes VII grade science students SMPS Islam Al-Asma Safari Bagan Siapiapi Academic Year 2015/2016. The research was conducted in classes VII SMPS Islam Al-Asma Safari Siapiapi chart of the month from March to April in Academic Year 2015/2016. The research subject is class VII are 25 people consisting of 17 women and 8 men. This research is a classroom action research study parameters are student learning outcomes absorption, mastery learning, and group awards. The instrument used in this study is the syllabus, lesson plans, and Student Assignment Sheet (LTS) data collection instruments, namely postal sheet test, and UH. From the research results can be known absorption in the first cycle was 69.15% (or less), increase the second cycle into 82.52% (excellent). Mastery learning students in the first cycle is 36% (category complete) and the second cycle increased to 96% (category complete). It can be concluded the implementation of cooperative learning model jigsaw can improve learning outcomes VII grade science students SMPS Islam Al-Asma Safari Bagan Siapiapi Academic Year 2015/2016.Key words: cooperative type jigsaw , study results